Peningkatan Kemampuan Pemahaman Konsep Siswa pada Materi Dimensi Tiga Menggunakan AR: Kalkulator Geogebra 3D - Marito, Winanda (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to describe the use of AR: GeoGebra 3D Calculator in improving students' understanding of mathematical concepts in three-dimensional materials. This study uses a quantitative approach with a pseudo-experimental method. The sample consisted of 69 eleventh grade students from MAS Al-Washliyah 22, which was divided into an experimental group (35 students) using AR: GeoGebra 3D Calculator and a control group (34 students) using conventional methods. The data collection technique is carried out through a concept comprehension test, namely pretest and posttest. Data analysis was carried out quantitatively on the test results obtained using an independent t-test test for normalized gain. The results showed that the experimental group showed a significantly higher increase in average scores from pretest to postes compared to the control group. The results of the independent t-test of the postes scores showed that there was a significant difference between the two groups. The normalized gain analysis further confirmed that the experimental group achieved a higher improvement (0.61) than the control group (0.41), with a significant difference (t = 4.876, p <0.001). The results of this study show that the use of AR: GeoGebra 3D Calculator significantly improves students' understanding of concepts in three-dimensional materials compared to conventional methods